2019
DOI: 10.31234/osf.io/rtnu5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rationalization and reflection differentially modulate prior attitudes toward the purity domain

Abstract: Outside Western, predominantly secular-liberal environments, norms restricting bodily and sexual conduct are widespread. Moralization in the socalled purity domain has been treated as evidence that some putative violations are victimless. However, respondents themselves disagree: They often report that private yet indecent acts incur self-harm, or harm to one’s family and the wider community—a result which we replicate in Study 1. We then distinguish two cognitive processes that could generate a link between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Moreover, this correlation has been confirmed as robust by a recent meta-analysis (Hannikainen et al, 2020). On the manipulation side, Paxton, Ungar, and found that presenting participants with a strong argument in favor of tolerance and giving them time to deliberate leads them to be more tolerant of harmless violation, while Hannikainen and Rosas (2019) found that forcing participants to reflect on whether an action is harmful or not leads them to become more tolerant of harmless violation. Although these results show that reflection can sometimes lead to more utilitarian judgments when participants are nudged towards the utilitarian conclusion by considerations specifically relevant to utilitarian judgment, they do not show that reflection preferentially leads to utilitarian judgment in less specific contexts.…”
Section: Beyond Sacrificial Dilemmas: the Generality Problemmentioning
confidence: 99%
“…Moreover, this correlation has been confirmed as robust by a recent meta-analysis (Hannikainen et al, 2020). On the manipulation side, Paxton, Ungar, and found that presenting participants with a strong argument in favor of tolerance and giving them time to deliberate leads them to be more tolerant of harmless violation, while Hannikainen and Rosas (2019) found that forcing participants to reflect on whether an action is harmful or not leads them to become more tolerant of harmless violation. Although these results show that reflection can sometimes lead to more utilitarian judgments when participants are nudged towards the utilitarian conclusion by considerations specifically relevant to utilitarian judgment, they do not show that reflection preferentially leads to utilitarian judgment in less specific contexts.…”
Section: Beyond Sacrificial Dilemmas: the Generality Problemmentioning
confidence: 99%
“…776 Jossain määrin julkiset palvelut ja sen myötä työpaikat lisääntyivät yhä 1980-luvulla, mutta edelliseen vuosikymmeneen verrattuna vähän. 777 Keskustapuolueen kannalta tilanne oli erityisen haastava. Puolueen kivijalka, aluepolitiikka, oli ongelmissa, ja samaan aikaan pääkaupunkiseudulle tarvittiin ilmiselvästi lisää resursseja.…”
Section: Helsingin Apulaiskaupunginjohtaja Erkkiunclassified